Non-polynomial representations of orthotropic tensor functions in the three-dimensional case: an alternative approach - Jemioło, S.; Telega, J.J. (Archives of Mechanics, 1997)
The objective of this paper is to extend some of the results obtained in [1] to the three-dimensional case. Functional bases and generators for symmetric second-order orthotropic tensor functions are derived.